ESTIMASI HERITABILITAS SIFAT PERTUMBUHAN DOMBA EKOR GEMUK DI UNIT PELAKSANA TEKNIS PEMBIBITAN TERNAK-HIJAUAN MAKANAN TERNAK GARAHAN - Sumadi (Sumadi); Jatmika Prajayastanda; Nono Ngadiyono (Buletin Peternakan, 2014)
Sheep is one of popular ruminants in Indonesia, because sheep is one one of source of animal protein, and also easy and convenient in breeding. Therefor, they should be developed, preserved and increased through improvement of genetic quality by selection and mating control in the breeding program. Arrangement of a breeding program requires the values of genetic parameter namely heritability. The purpose of this study was to estimate the growth heritability value of Fat Tailed sheep in UPT PT-HMT Garahan, Jember, East Java. Data were collected from progeny, birth weight and weaning weight of Fat Tailed sheep from 2007 to 2012 in UPT-HMT Garahan, Jember. Data were corrected by sex, type of birth and weaning of age. Data were analyzed using the heritability of paternal halfsib correlations and nested method of analysis. The estimation of heritabilities using paternal halfsib correlation were 0.85±0.39; 0.89±0,41 and 0.67±0.37 for birth weight, weaning weight and pre weaning average daily gain (ADG). While, heritabilities estimated from nested method were 0.89±0,48 (h2 S); -0.11±0.33 (h2 D); 0.39±0.28 (h2 S+D); 0.71±0.50 (h2 S); 0.69±0.52 (h2 D);  0.70±0.33 (h2 S+D); 0.47±0.44 (h2 S); 0.72±0.56 (h2 D); 0.60±0.32 (h2 S+D) for birth weight, weaning weight an pre weaning ADG, respectively. All growth heritabilities of Fat Tailed sheep in high category.(Keyword: Fat Tailed sheep, Growth characters, Heritability)